The Effect of Acute Physical Exercise on Natural Killer Cells Populations and Cytokine Levels in Healthy Women - Estefania Quintana-Mendias; Judith M. Rodríguez-Villalobos; Argel Gastelum-Arellanez; Natanael Cervantes; Claudia E. Carrasco-Legleu; Gerardo Pavel Espino-Solis (MDPI AG, 2023)
Physical exercise generates a systemic response in the immune system. It has been observed that cell populations respond to exercise stimuli, especially Natural Killer cells, whose number increase within minutes of starting physical exertion. This study aimed to evaluate the acute effect of moderate- and high-intensity exercise on immunological markers in healthy women. As specific objectives, the percentages of CD3-CD56+ Natural Killer total cells, CD56brightCD16dim effector subpopulation, CD56dimCD16bright cytotoxic subpopulation, NKG2A inhibition receptor, NKG2D activation receptor, and NKT cells were analyzed. In addition, the levels of the cytokines IL-1β, IL-6, IL-8, IL-10, IL-12p70, and TNF and the chemokines CCL5/RANTES, CXCL9/MIG, CCL2/MCP-1, and CXCL10/IP-10 were also analyzed. Natural Killer total cells showed an increase in their percentage in both exercise protocols (p = 0.001 for the moderate-intensity group and p = 0.023 for the high-intensity group); however, only in the high-intensity exercise session was there an increase in the CD56dimCD16bright cytotoxic subpopulation (p = 0.014), as well as a decrease in CD56brightCD16dim effector subpopulation (p = 0.001) and their NKG2A inhibition receptor (p = 0.043). An increase in IL-6 was observed after the high-intensity exercise session (p = 0.025). Conclusions. Physical exercise influences immunological markers and shows an acute response to moderate- or high-intensity exercise.